An automatic fermentation nutrition system compared to a traditional one: fermentation performances and composition of white wines - Matteo; Clara Vitaggio; Fabrizio Ghinolfi; Filippo Amato; Luciano Cinquanta; Onofrio Corona (OENO One)
The Avaferm® automatic yeast nutrition system was tested in comparison to manual nutrition management during the fermentation of white wines. To evaluate the two approaches, a factorial experimental design with interaction was established consisting of the two ways of nutrition (Avaferm® and Control) and two white grape varieties (Catarratto and Chardonnay). The experiments were conducted on an industrial scale, ensuring the practical relevance of the findings. The parameters that underwent evaluation encompassed a wide range of aspects, including the fermentation kinetics of sugars, the use of α-amino nitrogen and ammonium, as well as the technological and aromatic volatile composition of the wines.